2004
DOI: 10.1111/j.1365-2559.2004.01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TTF‐1 and cytokeratins in primary and secondary epithelial lung tumours: correlation with histological type and grade

Abstract: Immunohistochemical expression of CKs and TTF-1 may be correlated with histological type and grade of lung primary epithelial tumours and may allow them to be distinguished from non-pulmonary carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(30 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…TTF-1 is generally expressed diffusely in thyroid tumors but TTF-1 immunoreactivity varies according to tumor type in lung tumors (6). The TTF-1 immunoreactivity rate in primary lung ACs has been reported to be 60% to 100% (6,(38)(39)(40)(41). Studies reporting a lower staining percentage have emphasized the reason as TTF-1 immunoreactivity being lower in mucinous ACs compared to nonmucinous cases (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…TTF-1 is generally expressed diffusely in thyroid tumors but TTF-1 immunoreactivity varies according to tumor type in lung tumors (6). The TTF-1 immunoreactivity rate in primary lung ACs has been reported to be 60% to 100% (6,(38)(39)(40)(41). Studies reporting a lower staining percentage have emphasized the reason as TTF-1 immunoreactivity being lower in mucinous ACs compared to nonmucinous cases (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 92%
“…TTF-1 is also used as a marker in the differential diagnosis of lung adenocarcinomas and pleural mesothelioma (6,36). While TTF-1 expression is less frequently seen (0-30%) in LCCs of the lung (39,40,44), this rate is even lower (0-21%) in SCCs of the lung (6,36,(38)(39)(40)44). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many types of nonpulmonary adenocarcinomas (such as endometrium, pancreas, breast and ovary) may be less than 50% positive for CK5/6 [43], it has been reported to be a sensitive and specific marker of lung squamous cell carcinomas (at 73-100% in tissue sections [11,44,45,46,47] and at 75-100% in cytology [41,48,49]). In our study, CK5/6 showed the best possible specificity (100%) for squamous cell carcinoma, but the sensitivity was 81%.…”
Section: Discussionmentioning
confidence: 99%
“…Further, their literature review indicated earlier studies with the same clone had not shown any positive staining among 131 primary CRCs and 52 metastatic CRC to the lung or liver 2. More recently, the 8G7G3/1 antibody has been reported not to produce any staining among 163 and 134 intrapulmonary CRC metastases and 50 primary CRCs 5. Despite all these opposing existing data, we have no doubts about the legitimacy of our findings because positive immunostaining was consistently reproduced despite our use of different antigen retrieval, primary antibody concentrations and detection systems.…”
mentioning
confidence: 95%